2005
DOI: 10.1002/14651858.cd004703.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal pre-peritoneal (TAPP) vs totally extraperitoneal (TEP) laparoscopic techniques for inguinal hernia repair.

Abstract: There is insufficient data to allow conclusions to be drawn about the relative effectiveness of TEP compared with TAPP. Efforts should be made to start and complete adequately powered RCTs, which compare the different methods of laparoscopic repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(125 citation statements)
references
References 34 publications
4
109
1
11
Order By: Relevance
“…Fibrin glue is also said to be hemostatic and thus incidences of hematoma are also decreased [5]. Various techniques of hernia repair including laparoscopic hernia repair and the complications of the procedure have been reported in many studies [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin glue is also said to be hemostatic and thus incidences of hematoma are also decreased [5]. Various techniques of hernia repair including laparoscopic hernia repair and the complications of the procedure have been reported in many studies [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…European Hernia Society guidelines and a Cochrane Database review found broadly consistent results showing a slight increase in injuries to internal organs and portsite hernias with TAPP, and more frequent conversions to other surgeries with TEP. 9,37 Synthetic mesh is well established as an effective component of open and laparoscopic inguinal herniorrhaphy, but it is associated with several notable risks beyond those most commonly described. Chronic pain, 38,39 vas deferens injury and occlusion, 40 and enterocutaneous fistulae have been reported following synthetic mesh repair.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, следует отме-тить, что при всем накопленном опыте, многочисленности различного рода пуб-ликаций отсутствует единая хирургичес-кая тактика при выборе метода лечения паховых грыж [3,4]. Мнения различных авторов о преимуществах и недостатках современных способов устранения пахо-вых грыж ТАРР и ТЕР порой весьма про-тиворечивы, и для точного сравнения не-обходимо провести ещѐ ни одно исследо-вание [5,6]. Одним из преимуществ ТЕР является отсутствие хронической боли, возникающей после фиксации сетки (по сравнению с TAPP-техникой).…”
Section: On Improvement Of Methods Endovideosurgical Hernioplastyunclassified